Difficulties in resuscitating adult skeletal injury and trauma: a systemic review - Al-ajmi, Turki Abdullah S.; Salah Al-hussain, Abdullah; Fuad Al-Abdulqader, Mohammed (International Surgery Journal, 2017)
Background: Trauma resuscitations are complicated, high-risk, and time-sensitive actions that need the coordination of different specialists arriving from multiple areas in the hospital. This systematic review aimed to understand the main key challenges of trauma resuscitations using a broad search in various database. Methods: A systematic review of published articles between the years 2000 and 2016 was conducted using different electronic databases such as PubMed, Medline and Embase to identify studies evaluating trauma resuscitations challenges. Different keywords were used in this study to recognize relevant articles. The titles of all articles were scanned in the first stage. Irrelevant articles were omitted and the abstracts of the rest articles were reviewed in the second stage. Finally, the full text of all articles which met the inclusion and exclusion criteria were reviewed and a data extraction sheet was made to summarize all the articles. Data were analyzed descriptively. Results: Twenty studies were reviewed including; RCT (3 studies), QRCT (5 studies), and descriptive study (12 studies). The results showed that there are four main trauma resuscitation challenges including pre-hospital challenges, error-related challenges, equipment and technical challenges, and finally general challenges. Conclusions: Trauma resuscitation is one of the most critical aspects of emergency care. It is necessary to promote resuscitation care and focus on patient outcomes in terms of mortality and more importantly, functional outcomes. Considering these main factors affecting trauma resuscitation will improve patients’ outcomes and help those who are engaged in providing services.